Monitoring by Auditors: The Case of Public Housing Authorities - Grein, Barbara Murray; Tate, Stefanie L. (The Accounting Review, 2011)
ABSTRACT We take advantage of the unique reporting requirements of nonprofit public housing authorities (PHAs) to study the effect of audits on financial information both generally and when there are management incentives to misreport financial data. There is little prior research on the effect of audit adjustments in nonprofit settings and conflicting research on how auditors react to management's incentives to misreport. We identify potential financial statement areas at risk of manipulation based on incentives specific to public housing authorities. Using pre- and post-audit financial data for almost 3,600 PHAs across seven years, we find that auditors make economically and statistically significant adjustments to PHA financial statements. In addition, we find evidence that audits appear to reduce potential management bias, particularly to reduce risks of overstatement. Overall, audits appear to matter in this nonprofit, low-litigation risk setting where there is a large concentration of non-Big 4 auditors.